Zakat Collection Optimization Strategy Through the Role of Digital Technology in West Java - Jalaludin Mahali; Irfan Syauqi Beik; Ahmad Juwaini; Qurroh Ayuniyyah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Purpose: This study aims to analyze the influence of digital technology, influencers, and amil competence on muzakki decisions in paying zakat through formal zakat institutions. The research integrates the Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB), and trust in zakat institutions to explain behavioral factors affecting zakat payment decisions in the digital era. Method: The study employs a quantitative approach using Structural Equation Modeling (SEM). Data were collected from muzakki in several regions of West Java, including Depok City, Bogor City, Bogor Regency, and Bekasi Regency. The analysis involves evaluating the measurement model, structural model, and hypothesis testing to determine the relationships among variables. Findings: The results indicate that digital technology significantly influences the Technology Acceptance Model, suggesting that perceived usefulness and perceived ease of use encourage muzakki to adopt digital zakat platforms. Influencers significantly affect subjective norms within the Theory of Planned Behavior, demonstrating that social influence through digital media can shape public attitudes toward paying zakat. Additionally, amil competence significantly affects trust in zakat institutions, which subsequently influences muzakki decisions to pay zakat through formal institutions. Implications: These findings highlight the importance of integrating digital transformation, social communication strategies through influencers, and strengthening professional competence of amil in optimizing zakat collection. The study contributes to the development of Islamic social finance literature and provides practical insights for zakat management institutions in designing effective strategies to increase zakat participation.